Smoking and Socio-demographic correlates of BMI - Peizhi Wang; Edimansyah Abdin; Rajeswari Sambasivam; Siow Ann Chong; Janhavi Ajit Vaingankar; Mythily Subramaniam (BMC, 2016)
Abstract Background The aim of the current study was to examine the associations between Body Mass Index (BMI) and socio-demographic factors and to examine the relationship between BMI, smoking status and ethnicity. Methods The Singapore Mental Health Study (SMHS) surveyed Singapore Residents (Singapore Citizens and Permanent Residents) aged 18 years old and above. BMI was calculated using height and weight which were self-reported by respondents. Socio-demographic characteristics and smoking status were recorded in a standardized data collection form. Results Six thousand and six hundred sixteen respondents completed the study (response rate of 75.9 %) which constituted a representative sample of the adult resident population in Singapore. Ethnicity, gender and education status were associated with obesity. There was an interaction effect between ethnicity smoking status, and BMI. Indian and Malay smokers were less likely to be obese compared to Chinese smokers. The relationship between ethnicity and BMI was thus reversed when smoking was taken into account. Conclusions The study identified certain subgroups and risk factors that are associated with obesity. There is a need for further research to explore and identify genetic, metabolic and ethnic differences that underlie the interaction between ethnicity and smoking status which affects BMI.